2006
DOI: 10.1016/j.cageo.2005.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Application of parallel computing to stochastic parameter estimation in environmental models

Abstract: Parameter estimation or model calibration is a common problem in many areas of process modeling, both in on-line applications such as real-time flood forecasting, and in off-line applications such as the modeling of reaction kinetics and phase equilibrium. The goal is to determine values of model parameters that provide the best fit to measured data, generally based on some type of least-squares or maximum likelihood criterion. Usually, this requires the solution of a non-linear and frequently non-convex optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…In this study, we will restrict ourselves to the DrEAM algorithm ("Differential Evolution Adaptive Metropolis", [28]), which is a generalization of DE-MC ("Differential Evolution Markov Chain", [24]). Both DE-MC and DrEAM are related to a class of Population Monte Carlo methods (see the literature review in [24]), which have been successfully used in hydrology research [25][26][27]. In DrEAM, one simultaneously releases Markov chains from an over-dispersed set of points in the parameter space.…”
Section: Multichain Methodsmentioning
confidence: 99%
“…In this study, we will restrict ourselves to the DrEAM algorithm ("Differential Evolution Adaptive Metropolis", [28]), which is a generalization of DE-MC ("Differential Evolution Markov Chain", [24]). Both DE-MC and DrEAM are related to a class of Population Monte Carlo methods (see the literature review in [24]), which have been successfully used in hydrology research [25][26][27]. In DrEAM, one simultaneously releases Markov chains from an over-dispersed set of points in the parameter space.…”
Section: Multichain Methodsmentioning
confidence: 99%
“…MCMC also have difficulty with narrow and skewed posterior distributions; these may be resolved by either transforming the unknowns yielding a better-behaved distribution (i.e., more circular) [66] or adapting the proposal distribution [72], particularly when dealing with high-dimensional problems [73]. An intuitive way to deal with higher dimensional problems (where a single chain may have difficulty visiting the entire space in a reasonable number of iterations) or problems where evaluating the posterior distribution is computationally expensive (where a single chain may not be able to take many steps in a reasonable amount of time) is to have multiple chains distributed among multiple CPUs in a parallel supercomputer; Population Monte Carlo methods to do so have been investigated [74,75].…”
Section: Markov Chain Monte Carlo Methodsmentioning
confidence: 99%
“…A. Vrugt (vrugt@lanl.gov) jectives to create the initial sample of points. The results presented in Vrugt et al (2003) have demonstrated that this alternative search strategy provides a computational efficient and robust alternative to multiobjective optimization.It is surprising however that TRW have not considered this second or alternative optimization strategy in their paper. I believe that this alternative sampling approach should have been used in conjunction with the various algorithms, to appropriately disseminate and implement the ideas presented in Vrugt et al (2003).…”
mentioning
confidence: 89%
“…A. Vrugt (vrugt@lanl.gov) jectives to create the initial sample of points. The results presented in Vrugt et al (2003) have demonstrated that this alternative search strategy provides a computational efficient and robust alternative to multiobjective optimization.…”
mentioning
confidence: 89%